Effect of temperature and type of inorganic acid in acidolysis of epoxy and polyurethane thermosetting resins. - Agutaya, Jonas Karl Christopher N. et al.
This study aims to determine the effect of temperature on the diffusion of strong inorganic acids, as a precursor to dissolution in epoxy and polyurethane thermosetting resins. Epoxy and polyurethane resins were immersed in 5M solutions of HNO₃, H₂SO₄ and HCl at 30°C, 50°C and 80°C. From the relative changes in weight over a period of 12 days, the distribution coefficients were determined. Results showed an increase in the value of the diffusion coefficient with temperature. Moreover, both resins dissolved only in nitric acid at 80°C. In both resins, the nitric acid diffused the fastest and proved to be the most effective decomposing agent for the two polymers.
Keywords: Polyurethanes; Inorganic acids; Diffusion; Acidolysis; Epoxy; Thermosets